Producing of nonwoven materials by electrospinning the biocompatible polymers with chitosan addition - Ishchenko, Olena; Plavan, Viktoriia; Resnytskyi, Ilya; Liashok, Irina (Technology audit and production reserves, 2018)
The object of research is biocompatible composite nanofiber nonwoven materials with antiseptic properties, obtained by the electrospinning method. One of the most problematic places is the creation of a nonwoven biocompatible composite material with bactericidal properties; it has not previously been converted into fibers by electrospinning through high energy and financial costs. The composition of biocompatible polymers is used: chitosan, polyvinyl acetate (PVAC) and polyvinyl alcohol (PVA). The electrospinning method on the capillary type laboratory installation with a «bottom-up» solution is proposed for the production of nonwoven polymeric materials. Biocompatible composite nonwovens with antiseptic properties are obtained. This is due to the fact that the proposed method of electrospinning allows to obtain nonwoven materials with a certain statistical distribution of fibers, has several features when a solution of chitosan in lactic acid is introduced into the composition. In particular, for the composition based on PVA, the proportion of fibers with a diameter of 0.5–0.62 μm increased by 9 %, while for compositions based on PVAc it decreased by 21 %. It is established that the optimal voltage of the electric field is 30 kV and the distance between the electrodes is 9–11 cm for the production of fibers from biocompatible PVA and PVAc with the addition of chitosan. As a result of studies of the morphological features of the fibers obtained by optical polarization microscopy, it has been proved that with certain parameters of electrospinning, fibers with a diameter from 0.5 to 1.6 μm are obtained. As a result of determining the statistical distribution of polymer fibers in nonwoven material in diameter, it has been found that 69–94 % of the fibers have a diameter of 0.5–0.72 μm. A part of the fibers obtained in the laboratory installation of capillary electrospinning correspond to the area of nano-dimensions, which opens up prospects for obtaining biocompatible nanofibers with antiseptic and fungicidal properties. Therefore, the production of polymer biocompatible nonwovens by electrospinning can be used to create therapeutic systems.